Wildland-Urban Interface Case Study: Land Conservation along the Suwannee River - Lauren McDonell; Martha C. Monroe (EDIS, 2010)
FR232, a 4-page illustrated fact sheet by Lauren McDonell and Martha C. Monroe, discusses how the Suwannee River Water Management District successfully used conservation easements to restrict development, protect natural resources, and improve ecology around the Suwannee. Includes references. Published by the UF School of Forest Resources and Conservation, February 2010.